White matter disease and cognitive impairment in FMR1 premutation carriers - Filley, Christopher M. (Neurology, 2015)
OBJECTIVE: This cross-sectional, observational study examined the role of white matter involvement in the cognitive impairment of individuals with the fragile X mental retardation 1 (FMR1) premutation. METHODS: Eight asymptomatic premutation carriers, 5 participants with fragile X tremor/ataxia syndrome (FXTAS), and 7 noncarrier controls were studied. The mean age of the asymptomatic premutation carriers, participants with FXTAS, and noncarrier controls was 60, 71, and 67 years, respectively. Magnetic resonance spectroscopy (MRS) and diffusion tensor imaging (DTI) were used to examine the middle cerebellar peduncles (MCP) and the genu and splenium of the corpus callosum in relation to executive function and processing speed. MRS measures were N-acetyl aspartate/creatine (NAA/Cr) and choline/creatine, and fractional anisotropy (FA) was used for DTI. Executive function was assessed with the Behavioral Dyscontrol Scale and the Controlled Oral Word Association Test (COWAT), and processing speed with the Symbol Digit Modalities Test. RESULTS: Among all 13 FMR1 premutation carriers, significant correlations were found between N-acetyl aspartate/creatine and choline/creatine in the MCP and COWAT scores, and between FA in the genu and performance on the Behavioral Dyscontrol Scale, COWAT, and Symbol Digit Modalities Test; a correlation was also found between FA in the splenium and COWAT performance. In all regions studied, participants with FXTAS had the lowest mean FA. CONCLUSION: Microstructural white matter disease as determined by MRS and DTI correlated with executive dysfunction and slowed processing speed in these FMR1 premutation carriers. Neuroimaging abnormalities in the genu and MCP suggest that disruption of white matter within frontocerebellar networks has an important role in the cognitive impairment associated with the FMR1 premutation.